2015
DOI: 10.3390/nu7115449
|View full text |Cite
|
Sign up to set email alerts
|

Examining Means of Reaching Adolescent Girls for Iron Supplementation in Tigray, Northern Ethiopia

Abstract: Background: Iron deficiency is the most prevalent nutritional deficiency in adolescent girls from the developing world. One of the recommended interventions to improve iron status in adolescent girls is iron supplementation. Yet the provision of iron supplements to adolescent girls proved to be a challenging task for the health systems across the developing world. Objective: The objective of the study was to examine means of reaching adolescent girls for iron supplementation in Northern Ethiopia. Methodology: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
(26 reference statements)
2
12
1
3
Order By: Relevance
“…Meanwhile, the mean DDS of the current study was consistent with a study done in India 5.75 [49], Amhara Region among female adolescents 5.6 [4], Tigray region among female adolescents 3.5 [50], and Bangladesh among adult females 4.28 [51].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the mean DDS of the current study was consistent with a study done in India 5.75 [49], Amhara Region among female adolescents 5.6 [4], Tigray region among female adolescents 3.5 [50], and Bangladesh among adult females 4.28 [51].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, milk consumption was 7.7% which is lower than the study conducted in India 37.25% [ 54 ], 79.2% in Iran [ 48 ], and 26.5% in Tigray Region [ 50 ]. This variation would be the socio-economic difference between the study participants and lack of animal source foods and water in the study area due to seasonal ELINO drought.…”
Section: Discussioncontrasting
confidence: 78%
“…Research in Vietnam on the factors related to the consumption of supplements, including iron, shows that the intention of women to take supplements, especially iron, is still low outside of pregnancy (Nechitilo et al 2016). Research carried out in Tigray, Ethiopia, revealed that adolescents do not consume iron tablets due to public awareness, misinterpreting that iron tablets are contraceptive pills, religious and moral influences, and a lack of trust in the value of the iron tablet (Mulugeta et al 2015). Some studies suggest that anaemia prevention programs in female adolescents were more effective when school-based (Mulugeta et al 2015;Rakesh et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research carried out in Tigray, Ethiopia, revealed that adolescents do not consume iron tablets due to public awareness, misinterpreting that iron tablets are contraceptive pills, religious and moral influences, and a lack of trust in the value of the iron tablet (Mulugeta et al 2015). Some studies suggest that anaemia prevention programs in female adolescents were more effective when school-based (Mulugeta et al 2015;Rakesh et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian yang dilakukan oleh Mulugeta et al (2015) menunjukkan bahwa masih terdapat remaja putri yang memiliki persepsi yang salah mengenai konsumsi zat besi. Anggapan bahwa zat besi merupakan pil kontrasepsi yang menyebabkan infertilitas, persepsi perasaan sakit setelah mengonsumsi zat besi, dan keraguan responden adalah hambatan potensial untuk suplementasi zat besi pada remaja perempuan dari komunitas penelitian tersebut [30] .…”
Section: Metodeunclassified